Corporate Social Responsibility in the Water Industry Sector - Nora Rodek Berkes; Zoltán Birkner; Tivadar Máhr (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
Corporate social responsibility is an important means of achieving sustainability. More and more companies recognize the fact that responsible operation has a number of results that supports sustainability and thereby the long-term competitiveness. The United Nations' Sustainable Development Goal 6 deals with the issue of Clean Water and Sanitation and to ensure sustainable water management. Previous research on the subject have revealed that most of the company executives are not aware of the elements of the CSR concept. This research examines the social responsibility of the Hungarian water industry. We wanted to know whether the water companies- who deal with water in the industrial and service sectors- operate in a responsible way, as the water is one of the Earth's most precious natural resources. The results of the research show the organizational factors that most contributes to responsible operation as well as the formed clusters based on the CSR intensity of the Hungarian water companies.
Keywords: M14; 330; Corporate Social Responsibility; responsible operation; management; water industry